2020
DOI: 10.3390/molecules25030619
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of Proteomic Indicators for Colorectal Cancer in Initial Stages of Development

Abstract: Background: Colorectal cancer (CRC) at a current clinical level is still hardly diagnosed, especially with regard to nascent tumors, which are typically asymptotic. Searching for reliable biomarkers of early diagnosis is an extremely essential task. Identification of specific post-translational modifications (PTM) may also significantly improve net benefits and tailor the process of CRC recognition. We examined depleted plasma samples obtained from 41 healthy volunteers and 28 patients with CRC at different st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 68 publications
1
47
1
Order By: Relevance
“…APOE, which has been proved to be up regulated in patients with colorectal cancer (Borgquist, Butt et al 2016). It has been reported that overexpression of APOE was related to the growth of tumor in the advanced stage and increaseds the risk of tumor metastasis and invasion (Kopylov, Stepanov et al 2020), which may be related to the key role of APOE in cell proliferation and DNA synthesis (Niemi and Yla-Herttuala 2002). Moreover,APOE is one of the regulators of PI3K/Akt/mTOR pathway, which plays an important role in cell migration and proliferation, therefore, APOE can promote tumor progression by enhancing cell polarity (Vergadi, Ieronymaki et al 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…APOE, which has been proved to be up regulated in patients with colorectal cancer (Borgquist, Butt et al 2016). It has been reported that overexpression of APOE was related to the growth of tumor in the advanced stage and increaseds the risk of tumor metastasis and invasion (Kopylov, Stepanov et al 2020), which may be related to the key role of APOE in cell proliferation and DNA synthesis (Niemi and Yla-Herttuala 2002). Moreover,APOE is one of the regulators of PI3K/Akt/mTOR pathway, which plays an important role in cell migration and proliferation, therefore, APOE can promote tumor progression by enhancing cell polarity (Vergadi, Ieronymaki et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…The complex of ITIH2 and hyaluronan plays a signi cant role in the in ammatory response and the high expression of ITIH2 is associated with poor outcome of NSCLC (Wu, Wang et al 2013). In addition, a strong link between the expression levels of ITIH2 and estrogen levels has been demonstrated, since ITIH2 contains an estrogen-binding domain which might be critical for metastasis and tumor growth because estrogen has a profound effect on extracellular matrix integrity (Kopylov, Stepanov et al 2020). At present, there is not much research on the role of ITIH2 in tumor growth and metastasis, which is also a potential direction for the study of tumor metastasis mechanism in the future CDH2 is a member of the cadherin family, which regulates many cellular processes including apoptosis, angiogenesis, and chemoresistance (Miao, Wang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We identified a portion of 57 believable PTM peptides corresponding to 29 proteins. Further data curation left only 25 proteins containing 42 PTMs in total, and of them 20 proteins with 29 PTMs were finally recovered as the most related to the group of CRC patients [17]. Among them, a conformational analysis was performed on six proteins containing 12 peptides with modified amino acid residues, for which intact 3D structures were annotated in the Protein Database (see Supplementary materials, Table S3).…”
Section: Recognition and Selection Of Protein Structuresmentioning
confidence: 99%
“…Samples were collected into pre-chilled EDTA-2K tubes and centrifuged at 4 • C for 10 min at 1500 g after gentle agitation. Plasma fraction (1 mL) was transferred into the new clean cryovials (nominal volume is 2 mL) and frozen at −80 • C until the use [17].…”
Section: Demographymentioning
confidence: 99%
See 1 more Smart Citation